2013
DOI: 10.1016/j.soard.2012.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Effect of preoperative body mass index on weight loss after obesity surgery

Abstract: Background Prior studies suggest individuals with body mass index (BMI) above vs. below 60 kg/m2 show lower percentage of excess body weight loss (%EBWL) following bariatric surgery. Objectives 1. Test whether conclusions drawn about the effect of preoperative BMI on postoperative weight loss depend on the outcome measure; 2. Test for evidence of a threshold effect at BMI=60 kg/m2 and; 3. Test the effect from surgery to 12-month, relative to 12- to 36-month, follow-up. Setting Large University-affiliated h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
29
2
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(39 citation statements)
references
References 17 publications
6
29
2
2
Order By: Relevance
“…It has been consistently reported that bariatric operations frequently lead to significant weight loss, which starts shortly after the surgical procedure, continues for some time and is thought to plateau for most individuals around 18 months after surgery, when maximal weight loss is reached. 9,[16][17][18][19][20][21] In our study, the GEE analysis suggested that the nadir of body weight loss occurs around the 4 th trimester after surgery, between the first and second years after surgery and this finding agrees with those previous reported.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…It has been consistently reported that bariatric operations frequently lead to significant weight loss, which starts shortly after the surgical procedure, continues for some time and is thought to plateau for most individuals around 18 months after surgery, when maximal weight loss is reached. 9,[16][17][18][19][20][21] In our study, the GEE analysis suggested that the nadir of body weight loss occurs around the 4 th trimester after surgery, between the first and second years after surgery and this finding agrees with those previous reported.…”
Section: Discussionsupporting
confidence: 93%
“…On the other hand, Ochner et al 17 found that greater initial BMI were associated with worse postsurgical weight loss outcomes, but recommended caution when making comparisons, since results may vary, depending on the weight loss measure chosen and the time of postoperative period. They argue that postsurgical weight loss occurs at a relatively steady rate in the first 12 months after surgery, regardless of preoperative BMI, and shows great variability among BMI categories after 12-month follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…This might imply that the lower the preoperative BMI, the better are the results obtained by bariatric surgery and LSG in particular. This finding is concordant with the study by Ochner et al (27) reporting that the effect of preoperative BMI was apparent, heavier individuals showed lower percentages of initial and excess weight loss, and that this effect was particularly apparent after the initial rapid weight loss phase during the first year, when patients with BMI <50 continued losing weight, while patients with BMI ≥50 regained significant weight. Another cohort study reported significant weight loss and improvement of T2DM, hypertension and dyslipidemia after LSG in 78 patients whose BMI was less than 50 (28).…”
Section: Discussionsupporting
confidence: 92%
“…When compared to White patients, obese Black patients are known to have a higher prevalence of obesity-related comorbidities, including hypertension and type II diabetes mellitus [12][13]. While obesity is highest among Black (47.8%) and Hispanic (42.5%) populations, the majority of patients who undergo bariatric surgery are White (89%) [14]. Black patients also have higher rates of super morbid obesity at the time of surgery when compared to White patients [15][16].…”
mentioning
confidence: 99%